The Hubungan antara Pendapatan, Penyakit Infeksi dan Pola Makan terhadap Kejadian Gizi Kurang pada Balita: Pendapatan, Penyakit Infeksi dan Pola Makan terhadap Kejadian Gizi Kurang pada Balita - Azrimaidaliza; Lifda Syarif; Resmiati (Universitas Airlangga, 2022)
Background: One of the main health problems faced by low to middle-income countries, including Indonesia is the problem of undernutrition in toddlers. According to the 2021 Indonesia Nutritional Status Survey, undernutrition problems still occur in many Indonesian toddlers with a prevalence of 17%. The occurrence of undernutrition in toddlers is influenced by various factors including income, infectious diseases, and diet. Objectives: This research aims to identify the main contributors to undernutrition in toddlers. Methods: Data on factors related to the nutritional status of toddlers in the working area of Seberang Padang Health Center were collected using a cross-sectional design. Sampling was carried out using simple random sampling method in order to obtain a sample of 136 toddlers aged 2-5 years. The nutritional status of children was collected through direct measurement of weight and height, and use a questionnaire that has been tested for validity and reliability. Results: The percentage of toddlers aged 2-5 years with an undernutrition status is 7.2% and of under-fives who are malnourished with stunting conditions is 2.2%. Families with low incomes experienced had more risk to have children with undernutrition status than families with high incomes (p=0.017; POR=6.463; CI=1.402-29.799). Also, undernutrition was significantly associated with poor diet (p=0.036; POR=5.997; CI=1.127-26.153) and a history of infectious disease (p=0.027; POR=5.650; CI=1.212-26.153). Conclusions: Family income, diet, and history of infectious disease are determinants of undernutrition among children under five. Education on balanced nutrition and a healthy and clean lifestyle must continue to be delivered on a regular basis through the collaboration of health institutions and health education institutions in order to overcome undernutrition and reduce the risk of infection among children under five.